A review of interplanetary discontinuities and their geomagnetic effects - Tsurutani, B.T.; Lakhina, G.S.; Verkhoglyadova, Olga P.; Gonzalez, W.D.; Echer, E.; Guarnieri, F.L. (My University, 2011)
Interplanetary discontinuities and their geomagnetic effects are reviewed for magnetospheric/space weather researchers. Discontinuities are particularly useful as diagnostics since they are clearly identifiable in interplanetary data and their geomagnetic effects are unambiguous most of the time. Directional discontinuities (DDs) are abrupt changes in the interplanetary magnetic field direction and plasma parameters. DDs may be rotational discontinuities (RDs), tangential discontinuities (TDs) contact discontinuities (CDs) or shocks (fast (FS), intermediate (IS) and slow (SS). Shocks can propagate in the direction of the driver (forward shocks or FSs) or opposite to the driver (reverse shocks of RSs). Discontinuities interacting with other discontinuities may create new discontinuities. Fast forward shocks (FFSs) are shown to energize trapped particles by compressive effects, cause dayside aurora, lead to the creation of new radiation belts and to trigger nightside sector magnetospheric substorms. Fast reverse shocks (FRSs) or reverse waves (RWs) lead to magnetospheric expansions and the cessation of geomagnetic activity. TD-bow shock interactions create hot flow anomalies (HFAs) which then lead to outward expansions of the local magnetopause and dayside auroral enhancements. Some DD crossings may cause sudden southward IMF turnings. These cause magnetic reconnection and energy input into the magnetosphere–ionosphere–magnetotail system. Substorms sometimes occur thereafter. DDs that entail northward IMF turnings may lead to the triggering of substorms.
Keywords: Interplanetary discontinuities; Shocks; Auroras; Substorms